Particles, fields, space-time from Thomson's electron to Higgs' boson - Pohl, Martin (Boca Raton : CRC Press, 2020)
Particles, Fields,Space-Time: From Thomson's Electron to Higgs' Bosonexplores the concepts, ideas, and experimental results that brought us from the discovery of the first elementary particle in the end of the 19th century to the completion of the Standard Model of particle physics in the early 21st century. The bookconcentrates on disruptive events and unexpected results that fundamentally changed our view of particles and how they move through space-time. It separates the mathematical and technical details from the narrative into focus boxes, so that it remains accessible to non-scientists, yet interesting for those with a scientific background who wish to further their understanding. The text presents and explains experiments and their results wherever appropriate. This book will be of interest to a general audience, but also to students studying particle physics, physics teachers at all levels, and scientists with a recreational curiosity towards the subject. Features Short, comprehensive overview concentrating on major breakthroughs, disruptive ideas, and unexpected results Accessible to all interested in subatomic physics with little prior knowledge required Contains the latest developments in this exciting field
OCLC-licensed vendor bibliographic record.
Keywords: Particles (Nuclear physics) -- History; SCIENCE / Applied Sciences; SCIENCE / Mathematical Physics; SCIENCE / Quantum Theory